Usage of cryptocurrencies to avoid sanctions - Paltarak, Mikita; de Batz de Trenquelléon, Laure Sabine Marie; Taušer, Josef; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
This thesis explores the potential for using cryptocurrencies to evade sanctions, with a focus on the European Union (EU) regulatory framework. The research examines the shortcomings of current cryptocurrency regulations and assesses the feasibility of bypassing sanctions through the use of digital assets. The goal of this study is to investigate the effectiveness of existing regulations in preventing the evasion of sanctions through cryptocurrencies and to identify gaps in the existing regulatory environment that may facilitate such activities. The research combines a theoretical examination of regulatory frameworks with practical experiments and interviews involving individuals who have attempted to evade sanctions using cryptocurrencies. The thesis is structured into five main sections: The first section briefly explains cryptocurrencies, their need for regulation, and the challenges faced in regulating them. The second section examines international and country-level regulatory frameworks, with a focus on the EU, and evaluates the existing intra-exchange regulations such as Anti-Money Laundering (AML) and Know Your Customer (KYC) policies. The third section discusses the usage of cryptocurrencies to avoid sanctions, with a particular emphasis on the Russia-Ukraine conflict, and explores different approaches taken by countries and individuals to evade sanctions using cryptocurrencies. The fourth section presents the barriers to sanctions evasion and the approaches to maintaining anonymity. The final chapter includes interviews with individuals who have attempted to evade sanctions using cryptocurrencies and an experimental assessment of the feasibility of such evasion using cryptocurrencies. The last section concludes the thesis, summarizing the main findings and implications for regulatory authorities.
Vedoucí práce: Laure Sabine Marie de Batz de Trenquelléon
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses